A PERAN GURU ASWAJA DALAM MENANAMKAN NILAI-NILAI MODERASI ISLAM DI SMP ISLAM MBAH BOLONG WATUGALUH DIWEK JOMBANG: PERAN GURU ASWAJA DALAM MENANAMKAN NILAI-NILAI MODERASI ISLAM DI SMP ISLAM MBAH BOLONG WATUGALUH DIWEK JOMBANG - Ernawati, Santi; Hosna, Rofiatul (Al Tadib : Jurnal Ilmu Pendidikan, 2024)
Abstract: Educational institutions allegedly play an active role in counteracting the seeds of radical Islam. The existence of the phenomenon of the birth of violence that occurs both from speaking loudly and doing everything is an example in the form of radicalism. This study discusses the implementation of Islamic moderation values in class IX at SMP Islam Mbah Bolong Watugaluh Diwek Jombang, the role of aswaja teachers in instilling Islamic moderation values in class IX at SMP Islam Mbah Bolong Watugaluh Diwek Jombang, and the supporting factors and inhibiting factors. This research includes research that has qualitative as its method while for the type that is chosen correctly the case study is the choice. The results of research conducted on the role of aswaja teachers in instilling Islamic moderation values in class IX at SMP Islam Mbah Bolong Watugaluh Diwek Jombang found that the implementation of Islamic moderation values in class IX at SMP Islam Mbah Bolong Watugaluh Diwek Jombang includes the implementation of the value of tawasuth, i' tidal, tasamuh, and tawazun, but more emphasis is placed on the value of tasamuh, the role of the aswaja teacher in instilling Islamic moderation values in class IX at SMP Islam Mbah Bolong Watugaluh Diwek Jombang includes a holistic or comprehensive role as well as supporting factors for the aswaja teacher in instilling these values the value of Islamic moderation in class IX at SMP Islam Mbah Bolong Watugaluh Diwek Jombang is that all teachers are ahlussunnah wal jama'ah, and there are many supporting reading books that can be used as references, while the inhibiting factor is because class IX is still a child, so it is necessary extra energy and strategy.